Maximal Efficiency of PSII as a Marker of Sorghum Development Fertilized With Waste From a Biomass Biodigestion to Methane - Romanowska-Duda, Zdzisława; Grzesik, Mieczysław; Janas, Regina (Frontiers in Plant Science, 2019)
The aim of experiments was to investigate of chlorophyll fluorescence analysis, as a marker indicating growth, vigour, energetic value and physiological activity of sorghum fertilized with wastes from methane fermentation in a distillery integrated with a biogas plant using corn grains as substrate. The sorghum plants grown outdoor in different climate and in pots and in field were fertilized with different doses of the waste or Apol-humus – a soil improver and Stymjod – a nano-organic-mineral fertilizer. The chlorophyll fluorescence parameters (initial ﬂuorescence Fo, maximum ﬂuorescence Fm, variable ﬂuorescence Fv (Fm-Fo) and the maximum PSII efficiency Fv/Fm, in comparison with plant development), chlorophyll content, gas exchange, activity of selected enzymes, element content in leaves and energetic value were studied. The wastes, applied to soil resulted in increased the ratio of variable to maximal ﬂuorescence (Fv/Fm). It was associated with the increased dynamics of plant growth, their health, element content in leaves, fresh and dry biomass and physiological activity of plants as evidenced by activity of acid and alkaline phosphatase, RNase and dehydrogenase, as well as by gas exchange: net photosynthesis, transpiration, stomatal conductivity, intercellular CO2 content and index of chlorophyll content in leaves. The fertilization with Apol-humus and Stymjod additionally increased maximal photochemical efficiency of PSII (Fv/Fm) of dark-adapted sorghum leaves and plant growth. The dose of 30 m3 ha-1 and 40 m3 ha-1 of the non-centrifuged and centrifuged wastes, respectively, was most efficient in increasing efficiency of PSII (Fv/Fm), plant development, biomass yield, physiological activity, nutrient content in leaves and energetic value. The results indicate that waste from methane fermentation can be used as a natural fertilizer in sorghum crops and this ensures recycling of wastes from biogas plants and environmental protection. The measurement values of chlorophyll fluorescence parameters were proportionally to the vigour, growth and physiological activity of the plants. The obtained results indicate that the chlorophyll fluorescence in sorghum plants is a non-destructive method for defining the degree of growth and may be as a marker of plant vigour, development and physiological activity expressed by gas exchange, activity of selected enzymes and elements content in leaves.